Rural Household Livelihood Strategies in the South Coast Tourism Area of Bantul Regency Facing the Covid-19 Pandemic - Liana Fatma Leslie Pratiwi; Siti Rokhimah; Alifah Firda; Rahma Alfiani (Jurnal Dinamika Sosial Ekonomi, 2022)
Rural communities are known to have a tough life survival strategy in the face of all kinds of shocks problem, both natural and economic shocks. They are also easy to adapt. The Covid-19 pandemic affects the economic activities of rural communities in tourist areas, causing the community have a difficulty to earn a living in tourist areas from an economic perspective. This study aims to determine the household strategies of rural communities in achieving sustainable livelihoods in the Coastal Tourism Area of Bantul Regency in Facing the Covid-19 Pandemic. The basic method used is descriptive analytical. The research location was taken on a new beach in Bantul Regency which was crowded with visitors in the last 5 years, namely Goa Cemara Beach (Sanden District) and Baru Beach (Srandakan District). The data analysis method used is descriptive analysis method. The livelihood strategies chosen by rural households are divided into three criteria, namely survival strategies, consolidation, or accumulation. The classification of strategies is carried out based on the household income of the community. The result of the research is that the rural household strategy used to support the achievement of sustainable livelihoods is dominated by the consolidation strategy. Consolidation strategies are mostly carried out by the community both before, during and after the Covid 19 Pandemic. Consolidated community households develop themselves in the use of assets for medium-term goals and have sufficient assets to support daily household livelihoods.